PENGUATAN KOMPETENSI MANAJERIAL BERBASIS KKNI (ANALISIS TERHADAP PROBLEMATIKA KOMPETENSI MANAJERIAL MAHASISWA PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM PASCASARJANA IAIN PURWOKERTO) - Sunhaji Sunhaji (Jurnal Penelitian Agama, 2017)
Abstract: This paper focuses on the problem of managerial commitment based on IQF. The IQF is an embodiment of the quality and identity of the Indonesian nation in relation to the national education system, the national job training system and the national equality assessment system owned by the Indonesian nation. The basic principle developed in the IQF is to assess a person's performance in scientific aspects, expertise, and skills in accordance with learning outcomes. One fundamental aspect is strengthening student competencies through various academic activities that support increased managerial competence, both intra-curriculum, and extra curriculum. By strengthening competencies in real terms, it is expected that graduates of study programs can be accepted or at least relevant to the world of work needed by the community. This type of research is qualitative research. The researcher explores in order to understand and explain the problems under study through intensive relationships with speakers, through interviews, observation, Forum Group Discussion, questionnaires and documentation studies. Data analysis is the process of systematically searching for and compiling data obtained from observations, interviews, FGDs, questionnaires and documentation by organizing data into categories, describing them into units, synthesizing, arranging into patterns, choosing which ones are important and which ones will be studied and make conclusions so that they are easily understood by themselves and others. The findings in this study outline the students have the same perception, namely the weakness or the lack of managerial lecture activities carried out in the form of practicum. This does not mean putting aside the delivery of material in a theoretical form, but it needs to be balanced between which material is practical and which is theoretical. There are five categories assessing the suitability of managerial programs, starting from very appropriate, appropriate, hesitant, inappropriate to very inappropriate. Of the five categories, 30% of informants stated that the current managerial competencies with the world of work are considered very suitable. Then 60% of the informants stated that it was appropriate and the remaining 10% stated that it was inappropriate. Doubtful and very inappropriate categories or choices of answers, each of which gets a percentage of 0%, this means that not one informant answered that. The student needs to strengthen managerial competencies Study Program of Islamic Education Management Postgraduate of IAIN Purwokerto can be grouped into three parts, namely strengthening in the process (academic), infrastructure, and cooperation (Lecturers). Keywords: Managerial Competence, Curriculum, IQF, Islamic education Management Study Program.